2012
DOI: 10.1212/wnl.0b013e31826e26a6
|View full text |Cite
|
Sign up to set email alerts
|

Serum lycopene decreases the risk of stroke in men

Abstract: This prospective study shows that high serum concentrations of lycopene, as a marker of intake of tomatoes and tomato-based products, decrease the risk of any stroke and ischemic stroke in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 37 publications
(34 reference statements)
4
47
0
1
Order By: Relevance
“…However, epidemiological studies have generated conflicting results regarding lycopene and stroke. For example, an inverse association between circulating lycopene and stroke risk has been reported in some prospective studies8915, whereas other studies that focused on dietary lycopene intake have found inconsistent associations with stroke risk; some have shown negative associations161718 and some have reported positive ones19. In view of this uncertainty, we conducted a meta-analysis to address the relationships between the intake of lycopene or tomato-based products, as well as circulating lycopene, and the occurrence or mortality of stroke, which is defined as risk of stroke in our present study.…”
mentioning
confidence: 88%
“…However, epidemiological studies have generated conflicting results regarding lycopene and stroke. For example, an inverse association between circulating lycopene and stroke risk has been reported in some prospective studies8915, whereas other studies that focused on dietary lycopene intake have found inconsistent associations with stroke risk; some have shown negative associations161718 and some have reported positive ones19. In view of this uncertainty, we conducted a meta-analysis to address the relationships between the intake of lycopene or tomato-based products, as well as circulating lycopene, and the occurrence or mortality of stroke, which is defined as risk of stroke in our present study.…”
mentioning
confidence: 88%
“…The mechanism is not clearly known, although reduction of blood pressure is thought to play an important role. A recent study reported that high plasma levels of lyocopene (e.g., found in tomatoes) were associated with a reduced risk of stroke by 50% [63]. Moderate consumption (3-4 cups) of coffee or tea has been shown to reduce stroke risk as compared with no consumption [64,65].…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…Carotenoid lycopene is a particularly beneficial carotenoid; it aids in the prevention of coronary heart disease [14], myocardial infarction [15,16], and ischemic strokes [17], as well as for deceleration of early atherosclerosis' progression [17,18]. It can also lower systolic blood pressure [19].…”
Section: Introductionmentioning
confidence: 99%